WORD-BUILDING TYPES OF NICKNAMES DERIVED FROM PERSONAL NAMES (ON THE MATERIAL OF THE RUSKA POLYANA DIALECT, CHERKASY REGION) - Лонська, Людмила (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
Nicknames take an important place in the regional antroponymy. They have their own peculiarities of the given dialect: they form the person’s sel-consciousness and self-identification; they also determine the person’s mentality formed by the history, customs, traditions and culture of the given region. That’s why investigations of this type of onyms have always been actual in modern linguistics. A nickname is beleived to be notonly a certain information code of a person, it also includes information of the given century, and it 96 creates nation’s cultural portrait. It is unofficial persons’ names that give us possibility to learn linguistic, cultural and historic processesin the Ukrainian people’s life. The analysis of nicknames from different regions offers different results; they are determined by the particular antroponymic situation in the given social environment. Purpose of the article is to single out word-building types of nicknames, motivated by personal names. Results. The analysis of our material gave us possibility to single out seven word-building types of nicknames derived from antroponymic names. Each of these types is represented by structural and semantic models. The most productive word-building type is the type of patronymic nicknames derived from men’s names of their ancestors – their fathers, grandfathers, grandgrandfathers. It includes 11 structural word-building models. Highly productive are the structural and semantic models with suffix «-их(а)», and «-к(а)». Matronymic nicknames are also widely used in the given dialect. They are usually derived from mothers’ names by means of the suffix «-ин(а)». We also examined compound and composite nicknames which are formed by means of truncated names and patronymics; they may also be formedby means two names (mainly men’s names). Conclusions. The analysis of the word-building peculiarities of nicknames derived from citizens’ antroponymic names of the given Middle Dnieper Region village indicates of both national tendency of this class of antroponyms formation and of particular features of onyms found in the lexical, phonetical and structural variants. They are connected with intralinguistic and extralinguistic factors.